Renal outcomes of simultaneous liver–kidney transplantation compared to liver transplant alone for candidates with renal dysfunction - Brennan, Todd V. (Clin Transplant, 2014)
It is unclear whether a concomitant kidney transplant grants survival benefit to liver transplant (LT) candidates with renal dysfunction (RD). We retrospectively studied LT candidates without RD (n = 714) and LT candidates with RD who underwent either liver transplant alone (RD-LTA; n = 103) or simultaneous liver–kidney transplant (RD-SLKT; n = 68). RD was defined as renal replacement therapy (RRT) requirement or modification of diet in renal disease (MDRD)-glomerular filtration rate (GFR) <25 mL/min/1.73 m(2). RD-LTAs had worse one-yr post-transplant survival compared to RD-SLKTs (79.6% vs. 91.2%, p = 0.05). However, RD-LTA recipients more often had hepatitis C (60.2% vs. 41.2%, p = 0.004) and more severe liver disease (MELD 37.9 ± 8.1 vs. 32.7 ± 9.1, p = 0.0001). Twenty RD-LTA recipients died in the first post-transplant year. Evaluation of the cause and timing of death relative to native renal recovery revealed that only four RD-LTA recipients might have derived survival benefit from RD-SLKT. Overall, 87% of RD-LTA patients recovered renal function within one month of transplant. One yr after RD-LTA or RD-SLKT, serum creatinine (1.5 ± 1.2 mg/dL vs. 1.4 ± 0.5 mg/dL, p = 0.63) and prevalence of stage 4 or 5 chronic kidney disease (CKD; 5.9% vs. 6.8%, p = 0.11) were comparable. Our series provides little evidence that RD-SLKT would have yielded substantial short-term survival benefit to RD-LTA recipients.